Cognitive and affective functions of aged subacute myelo‐optico neuropathy patients in Japan. Issue 5 (29th May 2015) - Kawahara, Yuko; Deguchi, Kentaro; Hishikawa, Nozomi; Kurata, Tomoko; Sato, Kota; Kono, Syoichiro; Omote, Yoshio; Ohta, Yasuyuki; Yamashita, Toru; Abe, Koji
Abstract Background Subacute myelo‐optico neuropathy was the first epidemic drug intoxication that affected many people in Japan in the 1970s. Aim More than 40 years later, we assessed the real conditions of subacute myelo‐optico neuropathy patients. Methods The present study examined current cognitive and affective functions, activities of daily living, and vascular endothelial function in aged subacute myelo‐optico neuropathy patients (n = 28) compared with age‐, sex‐, body mass index‐ and years of schooling‐matched normal controls (n = 141). Results Mini‐Mental State Examination, Hasegawa Dementia Scale‐Revised, Montreal Cognitive Assessment and Frontal Assessment Battery scores were not significantly lower in subacute myelo‐optico neuropathy patients, but the Geriatric Depression Scale was significantly higher without apathy. Computerized touch‐panel tests showed poor performance in the flipping cards game, arranging pictures game and beating devils game, whereas activities of daily living and vascular endothelial function were within normal limits. Conclusion The present study shows that subacute myelo‐optico neuropathy patients showed essentially normal cognitive function using standard cognitive assessments, although the touch‐panel tests detected some decline in subacute myelo‐optico neuropathy patients. Subacute myelo‐optico neuropathy patients presented a higher depression score without evident apathy, activities of daily living decline or vascular endothelial dysfunction.